2006
DOI: 10.1254/jphs.fp0050777
|View full text |Cite
|
Sign up to set email alerts
|

c-Jun N-terminal Kinase Contributes to Norepinephrine-Induced Contraction Through Phosphorylation of Caldesmon in Rat Aortic Smooth Muscle

Abstract: Abstract. Vascular smooth muscle contraction is mediated by activation of extracellular signalregulated kinase (ERK) 1 / 2, an isoform of mitogen-activated protein kinase (MAPK). However, the role of stress-activated protein kinase /c-Jun N-terminal kinase (JNK) in vascular smooth muscle contraction has not been defined. We investigated the role of JNK in the contractile response to norepinephrine (NE) in rat aortic smooth muscle. NE evoked contraction in a dosedependent manner, and this effect was inhibited b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 21 publications
0
25
1
Order By: Relevance
“…From these results, we suggest that the Syk pathway plays a crucial role in the regulation of both Ca 2+ -dependent and -independent contractions in response to receptor agonists in vascular smooth muscle. Furthermore, our present and previous results showed that ET-1 increased the phosphorylation of MAPK isoforms, and inhibitors of ERK1 / 2 and SPAK/ JNK significantly inhibited agonists-induced contractions (20,21,35,37). In contrast to the results of p38 MAPK, inhibitors of Syk and p38 MAPK did not attenuate the ET-1-mediated phosphorylation of ERK1/ 2 in RASMC.…”
Section: +contrasting
confidence: 61%
See 1 more Smart Citation
“…From these results, we suggest that the Syk pathway plays a crucial role in the regulation of both Ca 2+ -dependent and -independent contractions in response to receptor agonists in vascular smooth muscle. Furthermore, our present and previous results showed that ET-1 increased the phosphorylation of MAPK isoforms, and inhibitors of ERK1 / 2 and SPAK/ JNK significantly inhibited agonists-induced contractions (20,21,35,37). In contrast to the results of p38 MAPK, inhibitors of Syk and p38 MAPK did not attenuate the ET-1-mediated phosphorylation of ERK1/ 2 in RASMC.…”
Section: +contrasting
confidence: 61%
“…Moreover, the p38 MAPK inhibitor did not influence the contraction induced by high K + . These results suggest that the p38 MAPK pathway is important in the regulation of smooth muscle contraction, especially Ca 2+ -independent contraction (21,35,36). Previously we reported the results that receptor-agonist-mediated MAPK activity was not influenced by extracellular Ca 2+ in vascular smooth muscle (22).…”
Section: Discussionmentioning
confidence: 59%
“…ERK1/2, p38 MAPK and JNK have been shown to promote vascular smooth muscle contraction (3638). In the present study, we found increased ERK1/2, JNK and p38 MAPK activation in arterial tissues of CRP-treated rats.…”
Section: Discussionmentioning
confidence: 99%
“…There results imply that PI3K-mediated MAPK activity induced by EGF is not regulated by the Akt pathway. We have previously showed that a vasoconstrictor increases the activity of MAPK and phosphorylation of h-caldesmon in aortic strips from sham-operated and DOCA-salt hypertensive rats, which were inhibited by an inhibitor of MAPK (8,30). Furthermore, the basal tone mediated by MAPK was not associated with the Ca 2+ -dependent mechanisms in vascular smooth muscle from hypertensive rats (24).…”
Section: Discussionmentioning
confidence: 96%